Preface - Santos Ortíz, Carlos (2015)
Cervical cancer is a real public health problem in Peru and countries called developing world, a problem that could not be controlled despite having the weapons to do so. We refer to secondary prevention through cytological screening in industrialized countries has significantly lower rates of incidence and mortality of this malignancy. Apparently, there is no reason for this success is not repeated in developing countries, but a deeper analysis leads us to believe that the classic system based on cervical cytology requires frequent repetition of the screening test, trained personnel, resources and organization, elements that do not have most of these countries.